2019
DOI: 10.1103/physrevb.100.235446
|View full text |Cite
|
Sign up to set email alerts
|

Disorder-induced suppression of charge density wave order: STM study of Pd-intercalated ErTe3

Abstract: Pd-intercalated ErTe3 is studied as a model system for the interplay between a bidirectional two component charge density wave (CDW) state and disorder. Using scanning tunneling microscopy (STM), we show that introducing Pd-intercalants (i.e. disorder) disrupts the long-range order of both CDW states via the creation of dislocations, which appear associated with each CDW separately. While for weak disorder both CDW states continue to coexist throughout the sample, with no "domains" of one CDW direction or anot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…For these intermediate dopings (and possibly larger dopings at lower temperatures) the existence of peaks in the presence of disorder may signify the existence of a Bragg glass phase 46 , which is characterized by quasi-long-range order as well as a lack of unpaired dislocations. Such a phase has been reported in other CDW systems 47 , and indeed recent STM measurements on crystals of Pd x ErTe 3 reveal possible signatures of such a state 48 . Further high-resolution xray di↵raction studies are required to definitively establish this.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…For these intermediate dopings (and possibly larger dopings at lower temperatures) the existence of peaks in the presence of disorder may signify the existence of a Bragg glass phase 46 , which is characterized by quasi-long-range order as well as a lack of unpaired dislocations. Such a phase has been reported in other CDW systems 47 , and indeed recent STM measurements on crystals of Pd x ErTe 3 reveal possible signatures of such a state 48 . Further high-resolution xray di↵raction studies are required to definitively establish this.…”
Section: Resultssupporting
confidence: 60%
“…at 30 K. The intensity of the peak at the secondary CDW wavevector grows more slowly and the temperature dependence of the width levels of at approximately 90 K. Similar conclusions have recently been reached by STM measurements of Pd x ErTe 3 . 48 Previous measurements on pristine ErTe 3 25 have demonstrated that the integrated intensity of the peak The secondary CDW peaks show up weakly, and are strongest near the four Bragg peaks in the corner rather than the peak centered here. This is simply due to the structure factor of the material.…”
Section: Resultsmentioning
confidence: 72%
“…In the overshoot regime, after dampening of the initial oscillations, the order parameter can get trapped at the metastable local maximum despite an incipient recovery of the double-well ground state. However, in real systems, several microscopic processes, such as local modification of T c by crystal defects 54 , 55 , CDW nucleation and creation of topological defects 47 and coupling of the collective excitation to other phonons 36 , will screen against a pronounced critical slowing-down. However, such effects go beyond our current model.…”
Section: Resultsmentioning
confidence: 99%
“…Reproducing the proper topology of the phase diagram for the heavy rare earth compounds requires the inclusion of higher order terms. One such model has been explored to 8th order for the case of RTe 3 in the presence of disorder [34]. In the pristine case, we have found that adding the two possible sixth order terms Eq.…”
Section: Unidirectional Cdws In a Quasi-tetragonal Systemmentioning
confidence: 99%